Lanthanides Revealing Anthropogenic Impact within a Stratigraphic Sequence. (16th July 2014) - Gallello, Gianni; Pastor, Agustín; Diez, Agustín; Bernabeu, Joan
Abstract : Difficulties to differentiate between anthropogenic and natural processes in the formation of archaeological deposits are crucial for a correct interpretation not only of the actions involved in the development of archaeological sites, but also of their occupation-abandonment dynamics and the understanding of their spatial behaviors and relationship with the environment. We have carried out lanthanides (rare earth elements "REE") analysis to distinguish anthropogenic from natural stratigraphic units in sediments using the advantage of the high sensibility, precision, and accuracy of ICP-MS measurements. In the Neolithic site of Mas d'Is (Alacant, Spain), we have applied REE analysis in a huge stratigraphic sequence called Pit 6, which was known to contain a large anthropogenic component. Randomly collected soil samples were sequentially taken in order to identify anthropogenic soil formations and to prove the proposed method blind testing has been used. In the specific case of Mas d'Is excavation a recurring question is whether paleosols are at the origin of the human occupation of the sites or it was the occupation of this areas which triggered the paleosols development. Our purpose was to distinguish the degree of human contribution to paleosols formation between samples sequentially taken at few centimeters of distances in a giant stratigraphic sequence (Pit 6) employing REE analysis.